Prospects of cowpea protein as an alternative and natural emulsifier for food applications: Effect of pH and oil concentration - Oliveira, Maria Mariana Garcia de [UNESP]; Fessori, Ana Gabriela Baroni Wicher [UNESP]; Huamaní-Meléndez, Víctor Justiniano [UNESP]; Ferreira Júnior, Sérgio Luís [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Mauro, Maria Aparecida [UNESP] (Elsevier, 2025)
In response to the growing need to expand the knowledge base on novel, more sustainable protein sources, this study investigated the effectiveness of cowpea protein concentrate (CPC) as a natural emulsifying agent, examining the relationships between pH (3−11), oil concentration (2–10 %), and emulsion stability. pH and oil concentration significantly impacted droplet size distribution, with uniformity decreasing in the order of pH 9 > pH 11 > pH 7, which was attributed to droplet coalescence and flocculation. As evidenced by circular dichroism, alkalinity induced a slight increase in the beta-sheet content of CPC, while simultaneously reducing the alpha-helix content. Rheological analysis of CPC-stabilized emulsions revealed a transition from shear-thinning to thickening flow behavior at higher shear rates. At pH 7, viscosity decreased with increasing oil concentration, whereas this effect was less pronounced in alkaline media. Alkalinity also prevented aggregation of oil droplets when emulsions were heated. At pH 3 and 5, phase separation occurred within 24 h. Emulsions at pH 9 and 11 exhibited the highest stability over a 30-day storage period, while the lowest stability (pH 7) was correlated with increased particle mobility. In most cases, at neutral and alkaline pH, CPC proved to be an effective emulsifying agent, demonstrating its ability to enhance stability by preventing coalescence and sedimentation.
Keywords: Cowpea protein; Emulsifying agent; Particle size distribution; Plant protein; Rheological behavior; Thermal effects